PERAN KINERJA GURU DALAM PENGARUH KEMAMPUAN PEMANFAATAN TEKNOLOGI PEMBELAJARAN TERHADAP EFEKTIVITAS PEMBELAJARAN - Hamidah, Fitriati; Edy Mulyono, Sungkowo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of learning technology utilization on learning effectiveness through teacher performance. The research was conducted because the use of technology in schools does not always lead to effective learning if it is not supported by optimal teacher performance. The purpose of this study was to analyze the direct effect of learning technology utilization on learning effectiveness, the effect of teacher performance on learning effectiveness, the effect of learning technology utilization on teacher performance, and the mediating role of teacher performance in the relationship between learning technology utilization and learning effectiveness. This quantitative study used a causal research design. The population consisted of 66 teachers from public junior high schools in Mojosari District, all of whom were used as the sample through total sampling. Data were collected using questionnaires and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS. The results showed that learning technology utilization had a positive and significant effect on learning effectiveness, teacher performance had a positive and significant effect on learning effectiveness, and learning technology utilization had a positive and significant effect on teacher performance. In addition, teacher performance significantly mediated the relationship between learning technology utilization and learning effectiveness. These findings indicate that technology can improve learning effectiveness both directly and through improved teacher performance.